Left mediastinal node dissection after arterial ligament transection via video-assisted thoracoscopic surgery for potentially advanced stage I non-small cell lung cancer - Shibano, Tomoki; Tsubochi, Hiroyoshi; Tetsuka, Kenji; Yamamoto, Shinichi; Kanai, Yoshihiko; Minegishi, Kentaro; Endo, Shunsuke (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Left mediastinal node dissection during lung cancer surgery can be difficult because paratracheal and subcarinal lymph nodes are concealed by mediastinal structures. Arterial ligament transection (ALT) offers a wide surgical view of concealed mediastinal spaces, thus enabling extended en bloc lymph node dissection (LND). We analyzed surgical outcomes of patients who underwent extended LND after ALT via video-assisted thoracoscopic surgery (VATS) for potentially node-positive clinical stage I non-small cell lung cancer (NSCLC). Methods: We retrospectively investigated the medical records of 75 patients who had undergone extended mediastinal node dissection after ALT via VATS for potentially node-positive NSCLC at our centers during the period from September 2008 through November 2015. Operative data and rates of overall survival (OS), in addition to mortality and morbidity, were analyzed in relation pathological stage and nodal stage. Results: Operative time was 238±58 minutes, and an average of 32.7±12.9 hilar and mediastinal lymph nodes were dissected. Lymph node metastases were detected in 34 patients (6 pN1 patients, 27 pN2 patients, and 1 pN3 patient). Mediastinal lymph node metastases were detected around the carina (stations 2L, 4L, and 7) in 19 of 27 patients with pN2 cancer. Nineteen patients had a total of 24 postoperative complications. Recurrent nerve paralysis was the most frequent complication (n=11) but resolved in eight patients during follow-up. Survival rates at 3 and 5 years were 92.2%/88.4%, 100.0%/60.0%, and 87.7%/81.0% for p-stage I, II, and III, respectively, and 92.2%/88.4%, 100.0%/60.0%, and 87.4%/80.7% for pN0, pN1, and pN2, respectively. Conclusions: Extended mediastinal node dissection after ALT allowed detection of lymph node micrometastases in selected patients with potentially node-positive left NSCLC and may improve outcomes.